Short-Season Corn Cost-Return Budget in Southeast Kansas - Fausett, Marvin R. (My University, 1998)
This publication outlines the expected costs and returns for short-season corn in southeast Kansas.
MF993_1998_10
Keywords: MF993; Economics; Crops; MF